2009
DOI: 10.5194/acp-9-2129-2009
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of isoprene and sulphoxy radical-anions – a possible source of atmospheric organosulphites and organosulphates

Abstract: Abstract. Transformation of isoprene coupled with autooxidation of S IV in aqueous solutions was studied experimentally and by chemical-kinetic modelling over a broad range of solution acidities (pH=3-9) to complement the research on aqueous-phase and heterogeneous transformation of isoprene reported recently by many laboratories. Isoprene significantly slowed down the auto-oxidation in acidic and basic solutions, and accelerated it slightly in neutral solutions. Simultaneously, production of sulphate ions and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 36 publications
0
69
0
Order By: Relevance
“…All the organosulfate products identified in the experiments could be explained by radical mechanisms initiated by the addition of SO 4 − on the double bond of the parent compound, followed by addition or oxidation by OH radicals and/or oxygen (presented in –). To our knowledge, the formation of organosulfates by reactions of SO 4 − radicals has only been reported before for isoprene [ Rudziński et al , 2009], and only for diluted conditions, not for concentrated sulfate mixtures relevant for aerosols, as in this work.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…All the organosulfate products identified in the experiments could be explained by radical mechanisms initiated by the addition of SO 4 − on the double bond of the parent compound, followed by addition or oxidation by OH radicals and/or oxygen (presented in –). To our knowledge, the formation of organosulfates by reactions of SO 4 − radicals has only been reported before for isoprene [ Rudziński et al , 2009], and only for diluted conditions, not for concentrated sulfate mixtures relevant for aerosols, as in this work.…”
Section: Resultsmentioning
confidence: 81%
“…We will show that these new mechanisms are a likely explanation for their origin and have other important effects, such as producing surfactants and increasing the cloud‐forming efficiency (or “CCN” efficiency) of aerosols. The photochemistry of sulfate ions and radicals, and their reactions with unsaturated organic compounds have been studied before, but only for diluted conditions typical of cloud droplets [ Tang et al , 1988; Herrmann et al , 2000; Herrmann , 2003; Buxton et al , 2000; Rudziński , 2004; Rudziński et al , 2009]. To our knowledge, these radical processes are investigated in concentrated sulfate mixtures typical of aerosols for the first time in this work.…”
Section: Introductionmentioning
confidence: 98%
“…Seven different chemically distinct compounds based on the isoprene carbon backbone, containing epoxy, alcohol, nitrate, and/or sulfate functional groups, have now been identified in ambient SOA Claeys et al, 2004;Wang et al, 2005;Surratt et al, 2007;Altieri et al, 2009;Gómez-González et al, 2008;Surratt et al, 2008;Froyd et al, 2010). Some of these compounds are undoubtedly formed from gas phase processing (Perring et al, 2009a, b;Lockwood et al, 2010;Ng et al, 2008), of isoprene, while other compounds (such as organosulfates) clearly indicate that additional chemical processing is occurring on ambient SOA particles themselves (Cole-Filipiak et al, 2010;Paulot et al, 2009;Surratt et al, 2010;Chan et al, 2010;Minerath et al, 2008Eddingsaas et al, 2010;Szmigielski et al, 2010;Nozière et al, 2010;Rudzinski et al, 2009) We recently investigated some of the potential SOA-phase chemistry for isoprene-related compounds, and proposed an overall mechanism (shown in Fig. 1) that can rationalize the existence of five of the seven observed isoprene-derived SOA components (Darer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas Kleindienst et al (2006) reported the formation of highly 5 oxygenated products through OH radical oxidation, Riva et al (2016) proposed an alternative route through acid-catalyzed oxidation by organic peroxides. Isoprene organosulfates were also reported to occur in the aqueous-phase through the photooxidation or dark reactions of isoprene in aqueous solutions containing sulfate and sulfite moieties (Rudzinski et al, 2004(Rudzinski et al, , 2009Noziere et al, 2010). A detailed mechanism of this transformation has been tentatively proposed based on chain reactions propagated by sulfate and sulfite radical anions (Rudzinski et al, 2009) and confirmed by mass spectrometric 10 studies (Szmigielski, 2016).…”
mentioning
confidence: 99%
“…Isoprene organosulfates were also reported to occur in the aqueous-phase through the photooxidation or dark reactions of isoprene in aqueous solutions containing sulfate and sulfite moieties (Rudzinski et al, 2004(Rudzinski et al, , 2009Noziere et al, 2010). A detailed mechanism of this transformation has been tentatively proposed based on chain reactions propagated by sulfate and sulfite radical anions (Rudzinski et al, 2009) and confirmed by mass spectrometric 10 studies (Szmigielski, 2016). The acid-catalyzed formation of 2-methyltetrols was also suggested in aqueous phase oxidation of ISO with H2O2 (Claeys et al, 2004b).…”
mentioning
confidence: 99%